Perancangan Alat Bantu Analisis Rapid Entire Body Assessment (REBA) Berbasis Aplikasi Android - Dawi Karomati Baroroh; Ramadhan Ramadhan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Work posture analysis is important because the wrong work posture can cause discomfort and fatigue in workers that can cause musculoskeletal disorder (MSDs). Rapid entire body assessment (REBA) is one of semi-quantitative posture analysis methods that are sensitive to the risk of MSDs in various occupational types. REBA analysis is usually done manually, so it takes a long time and there is a possibility of error. Therefore, it is necessary to design an REBA tool based on Android application analysis to facilitate and accelerate in posture analysis. This paper designed a tool of REBA analysis based on the Android application using MIT App Inventor 2. Furthermore, verification tests, validation, and usability tests are performed on the application design. There is also time comparison of REBA analysis manually and by using application (case study in Small and Medium Industries Aluminum, Giwangan, Yogyakarta). The results of this study indicate that the design of REBA applications based on Android has met the verification and validation test. Based on the usability test performed using System Usability Scale (SUS) method, the value obtained is 63.5, which means quite useful. In addition, the results of comparative REBA analysis times indicate a significant difference between manual calculation time and using the application, with time savings of REBA analysis using application of 51.19%.